1976
DOI: 10.1002/fam.810010109
|View full text |Cite
|
Sign up to set email alerts
|

Burning plastics: Mechanisms of smoke formation

Abstract: Abstract-Quantitative pyrolysis gas chromatography studies have been conducted on three grades of crosslinked polyester resin formulated for improved resistance to surface spread of flame. Pyrolysis temperatures from 723 to 1273 K were used, and these values correspond to 'surface' temperatures of materials exposed to heat fluxes of 15-149 k W m-2 which are typical of conditions experienced in real fires. Comparison is made with earlier macro studies on the evolution of smoke from plastics materials exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The lack of reproducibility of chromatograms obtained from pyrolysis experiments has also been observed by others. Green et al 24 reported the coefficients of variation to be in the general range of 2-12% but as high as 10-20% for certain flame-retarded polyester for- mulations. Similarly, May and co-workers28 reported coefficients of variation of 0.9-12% in a study of the pyrolysis of paint samples, which changed to 5.5-32.9% when a drifting baseline was involved.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The lack of reproducibility of chromatograms obtained from pyrolysis experiments has also been observed by others. Green et al 24 reported the coefficients of variation to be in the general range of 2-12% but as high as 10-20% for certain flame-retarded polyester for- mulations. Similarly, May and co-workers28 reported coefficients of variation of 0.9-12% in a study of the pyrolysis of paint samples, which changed to 5.5-32.9% when a drifting baseline was involved.…”
Section: Resultsmentioning
confidence: 97%
“…The lack of reproducibility of chromatograms obtained from pyrolysis experiments has also been observed by others. Green et al 24 reported the coefficients of variation to be in the general range of 2-12% but as high as 10-20% for certain flame-retarded polyester for- The use of a capillary OV 101 column for the analysis of the volatiles enabled separation of the majority of the degradation products in a single run and eliminated the need for several columns. Degradation of the 20% bromine DBNPG polyesters at 530°C in air produced a mixture of organic products which gave rise to well over a 100 peaks in the capillary column chromatogram at maximum sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Both fire retarded and non-fire retarded fiber glass reinforced polyesters were tested. The results (Tables [17][18][19] showed that the fire retarded material was more toxic based on the estimated LC,, values (Table 20). In both the vented and nonvented tests the toxicity of the fire retarded polyester was similar to that of Douglas fir, which was greater than the non-fire retarded polyester.…”
Section: University Of Pittsburgh Test Protocolmentioning
confidence: 98%
“…Non-flaming combustion was achieved by an electrical radiant heater, while flaming combustion used four small butane burners. Exposures were vented (i.e., 8 1/min of fresh air were mixed continuously with the combustion products to total a circulation flow rate through both chambers of 16 15,16,17) showed that the fire retarded material was more toxic based on the estimated LC^q values (Table 18). In both the vented and non-vented tests, the toxicity of the fire retarded polyester was similar to that of Douglas fir which was greater than the non-fire retarded polyester.…”
Section: Nbs Smoke Chambermentioning
confidence: 99%
“…Hilado [39,40,41,42,43,44] also found polyester to be more toxic than cotton and a flame retarded poly- [16] Green [17] (°K) ( [18] 900°C [18] 900°C [19] Carbon Not detected.…”
Section: Nbs Smoke Chambermentioning
confidence: 99%